Dynamic analysis of 10 MW offshore wind turbines with different support structures subjected to earthquake loadings. (June 2022) - Yan, Yangtian; Yang, Yang; Bashir, Musa; Li, Chun; Wang, Jin
Abstract: This paper investigates the structural dynamics of 10 MW offshore wind turbines (OWTs) supported by different substructures (Monopile, Tripod and Jacket) under wind, wave, current and earthquake loadings. The support structures are modeled using ANSYS, a finite element models (FEM ) software package, by considering the nonlinear soil structure interaction (SSI ) effects and earthquake loadings. A spring-displacement method has been employed to model the earthquake excitations on the support structures. FAST and AQWA tools have been used to analyze wind and wave loads which are fed into ANSYS via a dynamic link library (DLL) as external loads for combination with the earthquake loads to predict the support structures' responses. Earthquakes of different magnitudes have been simulated in the study. Under the earthquake with a magnitude of 7 measured on a Richter scale, the tower top displacements of the tripod, jacket and monopile are 1.42 m, 1.75 m and 1.80 m, respectively. The relative position of the displacement trajectory of the tripod OWT is nearest to the centroid of the yaw bearing. The maximum stresses of the jacket and tripod are respectively 5.7 times and 2.3 times that of the monopile. The average stress of the jacket and tripod are respectively 0.74 times and 0.56 times that of the monopile. This phenomenon shows that the tripod and jacket have a good stability, but with a high risk of local failure under earthquakes. The responses of the piles are mainly dominated by the seismic loads, rather than the wind and current loads. It was observed that the piles of the jacket and tripod OWT, which have small diameters and thin wall thickness, are more sensitive to earthquakes. Thus, the jacket and tripod OWTs may rely on the large stiffness offered by substructures to improve their stability. These phenomena can provide powerful insight into the seismic design of different substructures.